Fragile X syndrome: panoramic radiographic evaluation of dental anomalies, dental mineralization stage, and mandibular angle (Journal of Applied Oral Science, 2016)
Fragile X syndrome (FXS) is a disorder linked to the chromosome X long arm (Xq27.3), which is identified by a constriction named fragile site. It determines various changes, such as behavioral or emotional problems, learning difficulties, and intellectual disabilities. Craniofacial abnormalities such as elongated and narrow face, prominent forehead, broad nose, large and prominent ear pavilions, strabismus, and myopia are frequent characteristics. Regarding the oral aspects, deep and high-arched palate, mandibular prognathism, and malocclusion are also observed. Objective: The purpose of this study was to evaluate the dental radiographic characteristics as described in 40 records of patients with panoramic radiography. Material and Methods: The patients were in the range of 6–17 years old, and were divided into two groups (20 subjects who were compatible with the normality standard and 20 individuals diagnosed with the FXS), which were matched for gender and age. Analysis of the panoramic radiographic examination involved the evaluation of dental mineralization stage, mandibular angle size, and presence of dental anomalies in both deciduous and permanent dentitions. Results: The results of radiographic evaluation demonstrated that the chronology of tooth eruption of all third and second lower molars is anticipated in individuals with FXS (p